2001
DOI: 10.1093/ndt/16.5.999
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysis modalities on serum AGE levels in end‐stage renal disease patients

Abstract: Treatment with the biocompatible polysulfone SF dialyser seems to be better suited to lower serum AGE levels and to eliminate their precursors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 27 publications
0
53
1
3
Order By: Relevance
“…The site evolves from a fatty streak into histologically complex lesions characteristic of fully fledged atherosclerosis. 10,[12][13][14] The present study showed that the intensity of the pentosidine staining was higher in the veins compared with the arteries, especially in the presence of type 2 DM. Tokgoz et al have reported that patients with ESRD have a higher tendency of getting vein thrombosis, 15 and the concomitant presence of diabetes and renal disfunction can enhance platelet activity and blood clot formation.…”
Section: Discussionmentioning
confidence: 84%
“…The site evolves from a fatty streak into histologically complex lesions characteristic of fully fledged atherosclerosis. 10,[12][13][14] The present study showed that the intensity of the pentosidine staining was higher in the veins compared with the arteries, especially in the presence of type 2 DM. Tokgoz et al have reported that patients with ESRD have a higher tendency of getting vein thrombosis, 15 and the concomitant presence of diabetes and renal disfunction can enhance platelet activity and blood clot formation.…”
Section: Discussionmentioning
confidence: 84%
“…Membranes with high permeability can, therefore, decrease blood AGEs by up to 60% 164 and up to 80% with high-flux polysulfone. 165,166 Lin et al 167 showed that online hemodiafiltration, a combination of both HF and HD, for .6 months in patients with uremia leads to a significant reduction in serum AGE levels. A recent study showed that convective therapies not only effectively cleared uremic toxins but also, decreased levels of inflammatory markers, such as IL-6.…”
Section: Inhibition Of Gastrointestinal Absorptionmentioning
confidence: 99%
“…Serum AGE circulate in the form of modified proteins or peptides and, in the case of pentosidine, also in their free form. 10 Glycated albumin is a type of albumin which is modified by Amadori glucose adducts and several studies have established that exposure of renal glomerular cells to non-enzymatically glycated albumin induces alterations in biosynthetic and signalling pathways that are involved in the pathogenesis of diabetic nephropathy. 11,12 Lamb et al 13 have found increased glycated albumin concentration in serum and dialysate of patients undergoing CAPD.…”
Section: Agementioning
confidence: 99%